ANTERO POSTERIOR POSITION OF MAXILLARY CENTRAL INCISORS IN RELATION TO THE FOREHEAD IN PAKISTANI POPULATION - Hussain, Mazhar; Faiza Malik,; Muhammad Noman,; Munawar Manzoor Ali,; Gulsana Hashmi,; Saba Sikandar, (Journal of Ayub Medical College Abbottabad, 2026)
Abstract Objective To determine the anteroposterior (AP) position of maxillary central incisors in relation to the forehead and examine the potential correlation between the AP positioning of maxillary central incisors and the inclination of the forehead in a cohort representing the Pakistani population. Materials and Methods A total of 100 orthodontic patients aged 13 years and older, without regard to gender of Pakistani descent, were enrolled in the study. Exclusions comprised individuals with absent or impacted maxillary central incisors, history of orthodontic treatment, craniofacial trauma, prior cosmetic dental procedures, or anterior prostheses/restorations. Participants' demographic data including age and gender were recorded. Forehead inclination and position of maxillary central incisor were assessed from smiling photographs. Pearson's correlation coefficient was used to evaluate the correlation between the anteroposterior (AP) positioning of maxillary central incisors and the angle of forehead inclination. Differences in the AP positioning of maxillary central incisors based on age and gender were analyzed using t-tests and ANOVA. Results The males were 44 (44%) and females were 56 (56%). The mean age was 26.47 ± 6.46 years. The mean value of incisor position in males (2.86 ± 1.73 mm) was a little higher than in females (2.55 ± 2.03 mm) but not statistically significant (p = 0.416). The correlation between incisor position and forehead inclination was moderately high (r = 0.672), and it was very highly statistically significant (p < 0.001). Conclusions The average values for maxillary incisor sagittal position and forehead inclination were determined. A moderately strong and highly statistically significant correlation was observed between incisor position and forehead inclination. No gender differences were identified, although variations were noted among different age groups. Keywords: Anteroposterior; Forehead; Incisor; Orthodontics